Studies on Periodontal Disease - Ekuni, Daisuke; Battino, Maurizio; Tomofuji, Takaaki; Putnins, Edward E.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana Press, 2014)
The chapters of Studies on Periodontal Disease comprise four parts. Part 1 provides basic sciences from the general to the particular. The findings of cell culture and animal models supply the mechanism between periodontal disease and oxidative stress. In part 2, human clinical studies are mainly addressed. The effects of periodontal therapy on circulating oxidative stress are also discussed. The relationships between periodontal disease and systemic diseases are examined in part 3. The involvement of oxidative stress and inflammation are discussed through in vivo and in vitro study results. Part 4 discusses future strategies, including the effects of antioxidants and nutrition on periodontal disease. This thorough examination of the relationship between oxidative stress and periodontal disease is essential reading for researchers in oxidative stress and periodontal clinicians, alike.
Part I: Oxidative stress in periodontal diseases (basic science) -- 1. Reactive oxygen species and antioxidant systems in periodontal disease -- 2. The role of protein oxidative modification in periodontal diseases -- 3. Association between oxidative stress and periodontal diseases in animal model studies -- 4. Expression of reactive oxygen species and junctional and pocket epithelium -- 5. DNA damage caused by oral malodorous compounds in periodontal cells in vitro -- 6. Apoptotic pathways triggered by oral malodorous compounds in periodontal cells -- 7. The role of p53 in carcinogenesis and apoptosis in oral tissues -- 8. Physiological roles of a periodontopathic bacterial membrane-bound quinol peroxidase -- Part II: Oxidative stress in periodontal diseases (clinical studies) -- 9. Periodontitis and oxidative stress: Human clinical studies -- 10. Effects of periodontal therapy on circulating oxidative stress -- 11. Roles of HMGB1 in periodontal disease -- 12. The inflammation as the connecting link between systemic diseases and periodontal diseases -- 13. Periodontitis and atherosclerosis -- 14. Periodontitis and liver diseases -- 15. Oxidative stress and Periodontal disease in Down syndrome -- Part IV: Future strategies (control of ROS, roles of nutrition/antioxidants and application to dentistry) -- 16. New theories and their clinical relevance about the onset and development of periodontal diseases -- 17. The role of nutrition in periodontal diseases -- 18. Effects of antioxidants on periodontal disease -- 19. Role of vitamin C and vitamin E in periodontal disease -- 20. Salivary biomarkers of oxidative stress associated with periodontal diseases.
Keywords: Life sciences; Dentistry; Cytology; Life Sciences; Oxidative Stress; Cell Biology; Dentistry; Apoptosis